2021
DOI: 10.1002/adts.202100263
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizable Double Perovskite Oxide Search via Machine Learning and High‐Throughput Computational Screening

Abstract: Double perovskite structures have great potential for applications in batteries, lighting devices, and energy‐harvesting materials. In this study, the synthesizability of ABB′O3 double perovskite materials is predicted using machine learning. The machine learning algorithms are validated by performing high‐throughput computational screening. First, material properties extracted from the Materials Project database are used as training data to develop models to predict the formation energy and convex hull energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…For the Hubbard U parameters (GGA + U) treating d electrons in transition metals, the following values were used: [24] 3.32 eV (Co), 3.7 eV (Cr), 5.3 eV (Fe), 3.9 eV (Mn), 4.38 eV (Mo), 6.2 eV (Ni), 3.25 eV (V), and 6.2 eV (W). Although these U values were adopted to be consistent with the MP database and the previous study, [25] further validation was performed by comparing the current bandgap values to those from using U eff values, suggested by Bo Cai et al [36] It demonstrated that the mean absolute difference between two methods was 0.14 eV in Table S3, Supporting Information, confirming that the usage of current U values was adequate. For k-point generation, a gamma-centered Monkhorst-pack was used with grids of 3 × 3 × 3 and 6 × 6 × 6 for geometry optimization and energy calculation, respectively.…”
Section: Methodsmentioning
confidence: 80%
See 3 more Smart Citations
“…For the Hubbard U parameters (GGA + U) treating d electrons in transition metals, the following values were used: [24] 3.32 eV (Co), 3.7 eV (Cr), 5.3 eV (Fe), 3.9 eV (Mn), 4.38 eV (Mo), 6.2 eV (Ni), 3.25 eV (V), and 6.2 eV (W). Although these U values were adopted to be consistent with the MP database and the previous study, [25] further validation was performed by comparing the current bandgap values to those from using U eff values, suggested by Bo Cai et al [36] It demonstrated that the mean absolute difference between two methods was 0.14 eV in Table S3, Supporting Information, confirming that the usage of current U values was adequate. For k-point generation, a gamma-centered Monkhorst-pack was used with grids of 3 × 3 × 3 and 6 × 6 × 6 for geometry optimization and energy calculation, respectively.…”
Section: Methodsmentioning
confidence: 80%
“…First, 145 chemical descriptors were constructed [ 26 ] using information from the MP database and the DP‐oxide studied earlier. [ 25 ] In addition, the space group number was used to confirm their efficient role in improving the prediction accuracy because chemical descriptors alone cannot identify polymorph structures. Then, the surrogate model for predicting the E form , E hull , and E g of the DP‐halide materials is developed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…30 In terms of predicting the synthesizability of perovskites, several approaches have demonstrated that ML with high-throughput computational screening has high functionality and high accuracy. ML can be used in predicting the thermodynamic properties of ABO 3type perovskites, 31,32 classifying the stable and metastable structures of ABO 3 structures based on convex hull energy, 33 and analyzing the correlation between the atomic information and ionic conductivity of ABO 3 perovskites. 34 Also, as a promising candidate for solar light-capturing photovoltaic materials, 11 Li(Na)-based perovskites among 15 000 candidates were selected through classification on the formation energy and bandgap.…”
Section: Introductionmentioning
confidence: 99%